Non contiguous-finished genome sequence and description of Enorma timonensis sp. nov. - Ramasamy, Dhamodaran (Michigan State University, 2014)
Enorma timonensis strain GD5(T) sp. nov., is the type strain of E. timonensis sp. nov., a new member of the genus Enorma within the family Coriobacteriaceae. This strain, whose genome is described here, was isolated from the fecal flora of a 53-year-old woman hospitalized for 3 months in an intensive care unit. E. timonensis is an obligate anaerobic rod. Here we describe the features of this organism, together with the complete genome sequence and annotation. The 2,365,123 bp long genome (1 chromosome but no plasmid) contains 2,060 protein-coding and 52 RNA genes, including 4 rRNA genes.